Assessment of Spontaneous Alternation, Novel Object Recognition and Limb Clasping in Transgenic Mouse Models of Amyloid-β and Tau Neuropathology - Miedel, Christian J.; Patton, Jennifer M.; Miedel, Andrew N.; Miedel, Edward S.; Levenson, Jonathan M. (Journal of visualized experiments, 2017)
Here we describe a staged, behavioral testing approach that can be used to screen for compounds that exhibit in vivo efficacy on cognitive and functional motor behaviors in transgenic mouse models of β-amyloidosis and tauopathy. The paradigm includes tests for spontaneous alternation in a Y-maze, novel object recognition, and limb clasping. These tests were selected because they: 1) interrogate function of cognitive or motor domains and the correlate neural circuitry relevant to the human disease state, 2) have clearly defined endpoints, 3) have easily implementable quality control checks, 4) can be run in a moderate throughput format, and 5) require little intervention by the investigator. These methods are designed for investigators looking to screen compounds for activity in short-term and working memory tasks, or functional motor behaviors associated with Alzheimer's disease mouse models. The methods described here use behavioral tests that engage a number of different brain regions including hippocampus and various cortical areas. Investigators that desire cognitive tests that specifically assess cognition mediated by a single brain region could use these techniques to supplement other behavioral tests.